First Principles Study of Mechanical Properties and Electronic Structures of Vanadium‐Doped TiC and TiN. Issue 10 (26th June 2018) - Sun, Shuting; Liu, Yangzhen; Fu, Hanguang; Guo, Xingye; Ma, Shengqiang; Lin, Jian; Guo, Gencai; Lei, Yongping; Wang, Ruzhi
Abstract : The mechanical properties and electronic structures of TiC and TiN with different doping ratio of vanadium (V) are studied in this work using the first principles calculations. The simulation results show that Ti1− x V x N has lower formation energy than Ti1− x V x C, suggesting higher chemical stability of Ti1− x V x N. Ti0.25 V0.75 C and TiN show larger hardness than other Ti1− x V x C and Ti1− x V x N compounds. The anisotropic Young's modulus of Ti1− x V x C and Ti1− x V x N models are plotted in 3D surface constructions, and VN exhibited the strongest anisotropy. The uniaxial tensile simulation of Ti1− x V x C and Ti1− x V x N are conducted along [111] direction. The tensile strength of Ti1 −x V x N is stronger than Ti1 −x V x C. The tensile strength increases with the increasing of V‐doping ratio. Furthermore, the electronic structures of Ti1− x V x C and Ti1− x V x N are estimated. The modeling techniques used in this work and the calculation results are helpful for systematically understanding the properties of Ti1− x V x C and Ti1− x V x N in nanoscale. Abstract : The mechanical properties and the electronic structures of TiC and TiN with different doping ratio of vanadium (V) are studied in this work using the first principles calculations. The results are helpful for systematically understanding the properties of Ti1− x V x C and Ti1− x V x N in nanoscale.